Miss Lou Speaks about River Maid : Ribba Muma - Miss Lou, (Louise Simone Bennett-Coverley), 1919-2006; Bennett-Coverley, Louise, (Louise Simone Bennett-Coverley), 1919-2006 (Kingston, Jamaica : J.I.S., 1973)
Short monologue feature with Miss Lou recalling legends about Ribba Muma (River Mermaid).
Title taken from title screen.
Louise Bennett-Coverley
Jan. 1973
Also available as VHS tape and film reel.
Keywords: Storytelling -- Jamaica; Folklore -- Jamaica; Culture; Women folklorist -- Jamaica; Folk tales; Legends